Educational Game Design For Carbon Emission Using Game Development Life Cycle Method - Tresnawati, Dewi; Rahayu, Sri; Maulana, Randi (ULTIMATICS, 2024)
Carbon emissions are gases that arise from human actions, such as burning fossil fuels and industrial waste. Climate change is currently a problem that is increasingly attracting the attention of the wider community worldwide, including Indonesia. The educational game about carbon emissions applies the Game Development Life Cycle (GDLC) approach, which consists of six stages, including initiation, pre-production, production, testing, beta, and launch. The educational game on carbon emissions is expected to help raise youth awareness about the importance of reducing carbon emissions and provide information about efforts to reduce carbon emissions for the younger generation and the general public.